Abnormalities in microbial composition and function in infants with necrotizing enterocolitis: A single-center observational study - Huang, Huan; Peng, Qian; Zhang, Yuli; Li, Ying; Huang, Nanqu; Duan, Miao; Huang, Bo (Frontiers in Pediatrics, 2022)
Objective To investigate the features and functions of the intestinal microbiota in neonates with necrotizing enterocolitis (NEC) in a single center in China. Methods We collected clinical information and stool samples from 19 participants in our center, including 9 infants with necrotizing enterocolitis and 10 control infants. DNA was extracted from the samples, and 16S rRNA gene sequencing was used to analyse the participants' gut microbiota. Functional prediction was achieved using PICRUSt2. Results Alpha diversity analysis found that similar levels of bacterial richness and diversity were found in the gut microbiota of infants with NEC and control infants (P=0.1800), whereas beta diversity analysis suggested that the overall structures of the gut microbiota were significantly different (P=0.0020). The Mann‒Whitney U test of bacterial composition and abundance analysis revealed that the abundance levels of Proteobacteria (P=0.03049) and Firmicutes (P=0.01011) significantly differed between the two groups at the phylum level. Proteobacteria was the most abundant phylum in the NEC group. At the genus level, the abundance levels of Enterococcus (P=0.0003), Streptococcaceae (P=0.0109) and Lactobacillales (P=0.0171) were significantly decreased in infants with NEC. Furthermore, the linear discriminant analysis effect size (LEfSe) method showed 12 bacterial taxa with significant differences in relative abundances in the two groups. Interestingly, members of Proteobacteria were enriched in NEC samples. In addition, functional prediction suggested that the microbial changes observed in infants with NEC resulted in a decline in galactose metabolism, the pentose phosphate pathway, fructose and mannose metabolism, amino sugar and nucleotide sugar metabolism, glycolysis/gluconeogenesis, starch and sucrose metabolism, and phosphotransferase system (PTS) pathways (P<0.05). Conclusions Our study shows the compositional and functional alterations of the intestinal microbiota in NEC, which will help demonstrate the relationship between the gut microbiota and NEC pathogenesis.